Postępowanie fizjoterapeutyczne w hipotonii przepony – opis przypadku = Physiotherapy in hypotension diaphragm - a case study - Kochański, Bartosz; Plaskiewicz, Anna; Ratuszek, Dorota; Cichosz, Michał; Wołowiec, Łukasz; Dylewska, Monika; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Kochański Bartosz, Plaskiewicz Anna, Ratuszek Dorota, Cichosz Michał, Wołowiec Łukasz, Dylewska Monika, Zukow Walery. Postępowanie fizjoterapeutyczne w hipotonii przepony – opis przypadku = Physiotherapy in hypotension diaphragm - a case study. Journal of Education, Health and Sport. 2015;5(6):433-440. ISSN 2391-8306. DOI 10.5281/zenodo.19029 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A433-440 https://pbn.nauka.gov.pl/works/573170 http://dx.doi.org/10.5281/zenodo.19029 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 24.06.2015. Postępowanie fizjoterapeutyczne w hipotonii przepony – opis przypadku Physiotherapy in hypotension diaphragm - a case study Bartosz Kochański1, Anna Plaskiewicz1, Dorota Ratuszek1, Michał Cichosz2, Łukasz Wołowiec3, Monika Dylewska4,Walery Zukow5 1Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 2Jolly Med Szpital rehabilitacyjny Popielówek. Oddział rehabilitacji neurologicznej 3Studenckie Koło Naukowe Diagnostyki i Terapii Niewydolności Serca, II Katedra Kardiologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 4Bydgoska Szkoła Wyższa w Bydgoszczy 5Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Przepona jest głównym mięśniem oddechowym człowieka - wykonuje aż dwadzieścia tysięcy cykli pracy w ciągu doby. Dysfunkcje przepony mogą wpływać na powstawanie zaburzeń w narządzie ruchu oraz nieprawidłowości w biomechanice i wzorcach oddychania. Jednym z typów dysfunkcji przepony jest hipotonia przepony. W pracy przedstawiono przypadek pacjenta z hipotonią przepony. Na przykładzie omawianego pacjenta zaprezentowano obraz kliniczny oraz postępowanie fizjoterapeutyczne w hipotonii przepony. Abstract The diaphragm is the main respiratory muscle - performs up to twenty thousand cycles per day. Dysfunction of the diaphragm can influence by disturbances in the organ movement, and irregularities in biomechanics and breathing patterns. One of the types diaphragm dysfunction is hypotension diaphragm. The paper presents a case of a patient with hypotension diaphragm. The paper presents clinical picture and physiotherapy in hypertension diaphragm. Słowa kluczowe: przepona, oddychanie, hipotonia przepony. Keywords: diaphragm, breathing, hypotension diaphragm.